Analysis of Liquid Crystal Tunable Thin-Film Optical Filters Using Signal Flow Graph Technique - Athamneh, Abedalgany; Alboon, Shadi A. (International Journal of Optics, 2021)
In this paper, a liquid crystal tunable thin-film optical bandpass filter is studied and analyzed using the signal flow graph technique. This paper investigates an exact form for calculating the transmission coefficients, reflection coefficients, and the transmission intensity of the filter. The simulation results show the filter performance and the channel shape profile. In addition, the results show the tuning capability of the filter. The signal flow graph technique provides an attractive method for analyzing the thin-film optical filters since it overcomes the difficulty of the refractive index concept in extending to optical applications. Moreover, it simplifies the filter analysis and design process.